2022
DOI: 10.1186/s12967-022-03467-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced epinephrine promotes epithelial-to-mesenchymal transition and stemness of CRC through the CEBPB/TRIM2/P53 axis

Abstract: Background Previous studies have indicated that chronic emotional stressors likely participate in the occurrence of cancers. However, direct evidence connecting stress and colorectal cancer development remains almost completely unexplored. Methods Chronic stress mouse model was used to investigate the influence of stress on tumorigenesis. Several major agonists and antagonists of adrenergic receptors were applied to investigate the effects of β-adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…However, large population-based case-control studies have not confirmed alterations in risk for invasive breast carcinoma with β-blocker use. 39 This suggests that there may be other important factors involved in the process of chronic stress-promoting tumor progression. In this study, we revealed the presence of a chronic stress-activated adrenoceptor beta 2/PlexinA1 signaling pathway, which promoted cell proliferation and EMT of GC.…”
Section: Discussionmentioning
confidence: 99%
“…However, large population-based case-control studies have not confirmed alterations in risk for invasive breast carcinoma with β-blocker use. 39 This suggests that there may be other important factors involved in the process of chronic stress-promoting tumor progression. In this study, we revealed the presence of a chronic stress-activated adrenoceptor beta 2/PlexinA1 signaling pathway, which promoted cell proliferation and EMT of GC.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of B2AR, MOR, and GSK3 by adrenaline and opioid drugs has been identified as a contributing factor to drug resistance, particularly in triple-negative breast cancer cases ( Rousseau et al, 2022 ). EMT induction in both tongue squamous cell carcinoma and colorectal cancer is facilitated by the activation of distinct signaling pathways ( Liu et al, 2018 ; Zhou et al, 2022 ). The impact of the β2-AR agonist salbutamol on EMT, migration, and invasion has been substantiated through the activation of the ERK phosphorylation pathway ( Lu et al, 2022 ).…”
Section: Mechanisms Of Tme Alterations Under Chronic Stressmentioning
confidence: 99%
“…Another study reported that MAGI3, as a novel substrate-binding subunit of E3 ligase, can recognize cMYC and regulate its ubiquitination and degradation, thereby regulating colon cancer progression [ 28 ]. Ubiquitination is an essential post-translational modification [ 29 ] and has been investigated in the context of cMYC proteins in various ubiquitination mechanisms in multiple cancers [ 30 32 ]. However, whether GABA regulates the ubiquitination of cMYC in colon cancer cells has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%